Achievement motivation as mediating factor in the relationship between personality and job performance relationship - Fatimah Wati Halim,; Arifin Hj Zainal, (Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Meta-analytic studies have consistently reported that job performance has a significant relationship with personality trait. However only a limited amount of research has been conducted to find the mechanisms that mediate this relationship. Thus this study attempts to examine the direct role of personality traits as predictors of job performance and the indirect influence of achievement motivation as a mediating variable. Personality measurement tools were adapted from Cattell and achievement motivation from Cassidy and Lynn. Job performance indicator was obtained from annual job performance evaluations. All three personality traits were integrated into a model that predicts job performance and achievement motivation. The model was tested using structural equation modelling (SEM) with a sample of 450 public administrator officers. Results of the model show that it has a goodness of fit and explains, achievement motivation is found fully mediate for the relationship between conscientiousness and agreeableness toward job performance. However, emotional stability directly influence job performance. All the predictors are found to contribute to 24% of the variance in job performance. Implication of the finding shows that emotional stability and achievement motivation can be the essential predictor in predicting job performance of future candidates followed by agreeableness and conscienstiouness.